Commercial Laboratory Reproducibility of Serum CTX in Clinical Practice. (28th August 2019) - Hindi, Sahar M; Vittinghoff, Eric; Schafer, Anne L; Silverman, Stuart; Bauer, Douglas C
ABSTRACT: In 2011, the International Osteoporosis Foundation and the International Federation of Clinical Chemistry and Laboratory Medicine selected serum collagen type‐I crosslinked C‐peptide (s‐CTX) as the reference standard for bone resorption. This study aimed to determine the within and between laboratory reproducibility for s‐CTX assays. To create standardized pools, serum was collected from 10 premenopausal and 10 postmenopausal women. Premenopausal sera were pooled to approximate a population with normal bone turnover; postmenopausal sera were pooled to approximate a population with high bone turnover; and a third pool was created from an equal proportion of the pre‐ and postmenopausal pools. Multiple identical aliquots from each pool were created and frozen; all were labeled as routine clinical specimens. To evaluate longitudinal laboratory reproducibility, an identical aliquot from each of the three pools was sent to four US commercial laboratories on five dates over a 6‐month period. To evaluate within‐run reproducibility, each lab received five identical aliquots from each pool on the fifth date. Three labs (Mayo, ARUP, and Quest) used the Roche Diagnostics Elecsys assay, and one (Esoterix/LabCorp) used the IDS‐iSYS assay. Reproducibility was assessed using the coefficient of variation (CV) with 95% confidence intervals (CIs). Labs were unaware of the investigation. Across labs, mean s‐CTX values were 423, 533, and 480 pg/mL for the premenopausal, postmenopausal, and mixed pools, respectively, but the means differed between labs ( p  < 0.001). The premenopausal pool longitudinal CVs ranged from 5.0% to 14.9%; the postmenopausal pool CVs ranged from 3.4% to 19.3%; and the mixed pool CVs ranged from 3.3% to 16.0%. The longitudinal reproducibility for Esoterix/LabCorp was higher (CV 13.9%; 95% CI, 10.1% to 22.2%) than for the other labs. Within‐run CVs were also higher for Esoterix/LabCorp (CV 8.6%; 95% CI, 6.3% to 13.6%) compared with the other labs (CVs 2.1% to 6.2%). In conclusion, the reproducibility of s‐CTX varied across US commercial labs, and was poorer for Esoterix/LabCorp, which used the IDS assay, compared with the other three labs, which used the Roche assay. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.